Revision of total hip arthroplasty using an anterior cortical window, extensive strut allografts, and an impaction graft: follow-up study. - Arif, M.; Sivananthan, S.; Choon, D.S.K. (2004)
Using an anterior cortical window in the femur to remove the old implant does not predispose to failure of the allograft to incorporate into the host bone.